Viscosity and Proteolysis of Yoghurt Using Ropy Strains, in the Presence of Bifidobacteria, as Compared to Those of Soyoghurt - T. W. Murti; M. J. Desmazeaud (Buletin Peternakan, 1995)
Abstrak dalam bentuk hard copy